KEGIATAN MENEMPEL KOLASE SEDERHANA TERHADAP KEMAMPUAN MOTORIK HALUS ANAK TUNAGRAHITA SEDANG DI SLB C - SOLICHAH, IMROATUS (Jurnal Pendidikan Khusus, 2015)
Abstract Mid mentally retardation children in SLBC Dharma Wanita Lebo Sidoarjo had obstacle in handling, holding, getting a pinch, tearing, and sticking, they required to be led in order that their fine motoric ability enhanced by doing sticking simple kolase activity. The purpose of this research was to prove the influence of sticking simple kolase activity toward fine motoric ability of mid mentally retardation in SLBC Dharma Wanita Lebo Sidoarjo. This research method used quantitative approach of pre experiment kind with “pre-experimental design (non design)” , “one group pretest – posttest design”, the data was collected by using test method (action test), observation, and documentation. Observation was used to obtain the data of fine motoric ability to mid mentally retardation children before and after giving treatment while the data of documentation was as the support or proof data that the research was really done. The research result indicated that to the initial observation / the average pretest obtained was 55,53 and after giving treatment, the final observation / the average observation obtained was 90,48. It indicated that there was significant enhancement. Zh value = 2,20 was greater than critic value 5% Zt = +1,96 which meant that Ho was refused and Ha was accepted. So it could be concluded that there was influence of sticiking simple kolase activity toward fine motoric ability of mid mentally retardation children in SLBC Dharma Wanita Lebo Sidoarjo.   Keywords: simple kolase, fine motoric